تعليم اللغة العربية في العصر الحديث: الابتكار الرقمي وتحسين جودة التعليم القائم على أهداف التنمية المستدامة - Dewi Qotrun Nada Najwa (Pascasarjana Universitas Islam Negeri Mataram, 2025)
ABSTRACT This article aims to analyze the role of digital innovation in enhancing the quality of Arabic language education and to examine its alignment with the Sustainable Development Goals, particularly SDGs 4 on quality education. The study employs a literature review method by examining theories of digital literacy, language learning, and contemporary educational policy documents. Data were collected from academic articles, scholarly publications, and relevant digital sources, and analyzed using a qualitative descriptive approach through content analysis. The findings indicate that the integration of digital technology such as gamification, interactive platforms, and learning applications significantly improves students’ motivation, engagement, and overall learning effectiveness in Arabic language education. However, the study also identifies implementation gaps, especially related to limited digital competencies among educators and the scarcity of high-quality Arabic educational content. These results suggest that digital innovation not only enhances learning quality but also promotes equitable access and strengthens cultural identity, contributing directly to inclusive and sustainable education. Therefore, digital innovation represents a strategic element in transforming Arabic language instruction in the modern era. Keywords: Arabic language learning, digital innovation, digital literacy, SDGs, sustainable education. الملخص يهدف هذا المقال إلى تحليل دور الابتكار الرقمي في تحسين جودة تعليم اللغة العربية، وتقييم ارتباطه بأهداف التنمية المستدامة، ولا سيما الهدف الرابع المتعلق بالتعليم الجيد. اعتمد البحث على منهج الدراسة المكتبية من خلال مراجعة معمّقة لنظريات محو الأمية الرقمية، وتعليم اللغات، والوثائق والتقارير التربوية المعاصرة. وقد استندت البيانات إلى مقالات علمية ومنشورات أكاديمية ومصادر رقمية ذات صلة، ثم جرى تحليلها باستخدام الأسلوب الوصفي النوعي عبر تحليل المحتوى. أظهرت نتائج الدراسة أن توظيف التكنولوجيا الرقمية—مثل التلعيب، المنصات التفاعلية، والتطبيقات التعليمية—يسهم بشكل ملحوظ في رفع الدافعية، وتعزيز المشاركة، وزيادة فعالية تعلم اللغة العربية. كما كشفت الدراسة عن فجوات واضحة في التطبيق، أبرزها ضعف كفاءة المعلمين الرقمية وقلّة المحتوى التعليمي العربي عالي الجودة. وتؤكد هذه النتائج أن دمج التكنولوجيا لا يرفع جودة التعليم فحسب، بل يعزز أيضًا الشمولية ويقوي الهوية الثقافية، مما يجعله عنصرًا مهمًا في تحقيق تعليم مستدام وشامل. وعليه، يُعدّ الابتكار الرقمي أداة استراتيجية لتطوير تعليم اللغة العربية في العصر الحديث. الكلمات المفتاحية: تعليم العربية، الابتكار الرقمي، محو الأمية الرقمية، أهداف التنمية المستدامة، التعليم المستدام.